Efektivitas Pembelajaran Kontekstual berbasis Outing Class dalam Mengembangkan Kemampuan Berbahasa pada Anak Usia Dini - Putri, Naufa Melati; Afandi, Nur Kholik (Indo-MathEdu Intellectuals Journal, 2024)
Outing class-based contextual learning in developing language skills in young children needs to be done to avoid boredom in the learning process. Outing class learning provides an opportunity to express children's language skills. This research aims to determine the effectiveness of outing class-based contextual learning in improving early childhood language development. This type of research is qualitative research. The results of this research indicate that the outing class learning method is effectively applied in contextual learning to improve aspects of language development in early childhood. In the new normal period, this method is suitable to be applied in learning because it can eliminate the boredom of studying during the pandemic and can add direct experience so that it can improve children's language skills.